2008
DOI: 10.1590/s1415-98482008000300006
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade, salários e taxa de câmbio: uma análise da experiência brasileira nos anos 1990

Abstract: O propósito deste trabalho é analisar as relações entre salário real, produtividade, emprego e taxa de câmbio real na economia brasileira durante os anos 1990. Esse período é particularmente interessante, já que combinou liberalização comercial, valorização da moeda e aumentos elevados de produtividade. Com esse objetivo, testou-se, através de um modelo VEC, um modelo teórico baseado em concorrência monopolística. O modelo fez as previsões corretas quanto à relação salário real e produtividade, mas não quanto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…iii) why do different economic sectors present such varying rates of productivity and wage growth? This sectoral perspective complements previous analyses that examine labor productivity and income in Brazil on a national level (Romanatto et al, 2008).…”
Section: Introductionmentioning
confidence: 73%
“…iii) why do different economic sectors present such varying rates of productivity and wage growth? This sectoral perspective complements previous analyses that examine labor productivity and income in Brazil on a national level (Romanatto et al, 2008).…”
Section: Introductionmentioning
confidence: 73%
“…Sacconato and Menezes-Filho (2005) suggest that, in the period 1988-1995, productivity was one of the main determinants of differences between income levels in Brazil and in the U.S., as well as between wages in Brazilian high and low productivity sectors. Indeed, many studies (for example, Feldstein, 2008;Salvatore, 2008;Romanatto et al, 2008) found a positive relation between labor productivity and wage, though only a small share of gains from labor productivity may be translated into gains in real wages, as occurred in Brazil in the decades before the 1980s (Colistete, 2009).…”
Section: Economic Growth Productivity and Wages In Brazil And The Unmentioning
confidence: 99%